Implementation of Port Service Retribution Policy at Local Feed Port of Bandar Batauga in South Buton Regency - Karimali, Aswad; H, Herman; Halim, Didin; Andi Anugrah Mahyuddin (International Journal Of Public Policy and Bureaucracy, 2024)
This study aims to identify and describe the implementation process of port service levy policy and its internal and external factors. The type of research is descriptive qualitative. Data collection techniques through observation, interviews and documentation. Data analysis techniques include data condensation, data presentation, and drawing conclusions. The results of the study related to policy implementation show that the standards and targets of the port service levy policy at Bandar Batauga Port are good, with a good understanding of employees regarding Regional Regulation Number 7 of 2019 and policy targets that are in accordance with field conditions. However, its implementation has been hampered by limited facilities, infrastructure, and human resources that are not yet optimal. Human resources are also still inadequate, limited training for field officers and inadequate infrastructure are the main obstacles in policy implementation. The characteristics of the implementing organization, such as clear delegation of tasks and effective internal coordination, are good, with routine supervision that ensures the levy collection process runs according to standards. Communication between related organizations has been running smoothly, and cooperation between the Transportation Agency, Regional Revenue Agency, and State-Owned Enterprises is well established. The attitude of the policy implementers, although many are still interns with low wages, shows high dedication to their duties. The social, economic, and political environment supports this policy, although the minimal economic impact due to the inactive port is a challenge. Internal factors in the implementation of this policy are good, with good understanding from the implementers, but limited human resources and infrastructure are obstacles. External factors also support effective socialization and good public acceptance, although it is necessary to improve socialization methods and strengthen infrastructure to support the success of the policy. Keywords: Policy Implementation, Retribution Policy, Port Service, Internal and External Factors